Leishmania infantum infection modulates messenger RNA, microRNA and long noncoding RNA expression in human neutrophils in vitro - Scaramele, Natália Francisco [UNESP]; Troiano, Jéssica Antonini [UNESP]; Felix, Juliana de Souza [UNESP]; Costa, Sidnei Ferro [UNESP]; Almeida, Mariana Cordeiro [UNESP]; de Athayde, Flávia Regina Florencio [UNESP]; Soares, Matheus Fujimura [UNESP]; Lopes, Maria Fernanda da Silva [UNESP]; Furlan, Amanda de Oliveira [UNESP]; de Lima, Valéria Marçal Felix [UNESP]; Lopes, Flavia Lombardi [UNESP] (Public Library of Science (PLoS), 2024)
In the Americas, L. infantum (syn. chagasi) is the main cause of human visceral leishmaniasis. The role of neutrophils as part of the innate response to Leishmania spp. infection is dubious and varies according to the species causing the infection. Global expression of coding RNAs, microRNAs and long non-coding RNAs changes as part of the immune response against pathogens. Changes in mRNA and non-coding RNA expression resulting from infection by Leishmania spp. are widely studied in macrophages, but scarce in neutrophils, the first cell to encounter the trypanosomatid, especially following infection by L. infantum. Herein, we aimed to understand the expression patterns of coding and non-coding transcripts during acute in vitro infection of human neutrophils by L. infantum. We isolated neutrophils from whole blood of healthy male donors (n = 5) and split into groups: 1) infected with L. infantum (MOI = 5:1), and 2) uninfected controls. After 3 hours of exposure of infected group to promastigotes of L. infantum, followed by 17 hours of incubation, total RNA was extracted and total RNA-Seq and miRNA microarray were performed. A total of 212 genes were differentially expressed in neutrophils following RNA-Seq analysis (log2(FC)±0.58, FDR≤0.05). In vitro infection with L. infantum upregulated the expression of 197 and reduced the expression of 92 miRNAs in human neutrophils (FC±2, FDR≤0.01). Lastly, 5 downregulated genes were classified as lncRNA, and of the 10 upregulated genes, there was only 1 lncRNA. Further bioinformatic analysis indicated that changes in the transcriptome and microtranscriptome of neutrophils, following in vitro infection with L. infantum, may impair phagocytosis, apoptosis and decrease nitric oxide production. Our work sheds light on several mechanisms used by L. infantum to control neutrophil-mediated immune response and identifies several targets for future functional studies, aiming at the development of preventive or curative treatments for this prevalent zoonosis.